2013
DOI: 10.1080/17470218.2013.768276
|View full text |Cite
|
Sign up to set email alerts
|

Allocating Attention to Distractor Locations is Based on Top-Down Expectations

Abstract: Failures of selective attention may be explained by the attentional white bear (AWB) hypothesis maintaining that prior knowledge of distractor location causes attentional allocation to it. The AWB is demonstrated by embedding infrequent trials of two simultaneous dots among flanker trials. The dot at the expected distractor location is perceived as appearing before the dot at the expected empty location, indicating attentional allocation to expected distractor locations. A major requirement of the AWB hypothes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
5
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 11 publications
(19 reference statements)
2
5
1
Order By: Relevance
“…It is interesting to note that the present results are very different from those reported by Tsal and Makovski (2006;Humphreys et al, 2004;Lahav et al, 2012;Lahav & Tsal, 2013;Makovski, 2019). Tsal and Makovski (2006) had participants perform a classical flanker task (Eriksen & Eriksen, 1974), in which they were asked to report a centrally presented target while ignoring two diagonally arranged flanking distractors.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…It is interesting to note that the present results are very different from those reported by Tsal and Makovski (2006;Humphreys et al, 2004;Lahav et al, 2012;Lahav & Tsal, 2013;Makovski, 2019). Tsal and Makovski (2006) had participants perform a classical flanker task (Eriksen & Eriksen, 1974), in which they were asked to report a centrally presented target while ignoring two diagonally arranged flanking distractors.…”
Section: Discussioncontrasting
confidence: 99%
“…Overall, a large number of studies suggest that distractor suppression can only occur in a reactive manner (e.g., Beck et al, 2018;Humphreys et al, 2004;Lahav et al, 2012;Lahav & Tsal, 2013;Makovski, 2019;Moher & Egeth, 2012;Tsal & Makovski, 2006;Won et al, 2019). For instance, Moher and Egeth (2012) showed that if observers were instructed to ignore a particular distractor feature, target search was slower than in a neutral condition in which no prior feature information regarding the distractor was provided.…”
mentioning
confidence: 99%
“…Based on Stelmach and Herdman (1991), who showed that an attended stimulus was perceived to occur before an unattended stimulus, it was found that more attention was allocated to the location of the to-be-presented distractor than to an empty location. This surprising finding was later replicated (Lahav, Makovski, & Tsal, 2012; Lahav & Tsal, 2013) and generalized to feature-based attention as well. For instance, it was found that visual search was slowed down, rather than expedited, given a cue to ignore a distractor’s color (Moher & Egeth, 2012).…”
mentioning
confidence: 73%
“…The filtering setting can be held active to suppress the distractor processing only for a limited duration. A possible explanation for the limited activation of the spatial filtering settings lies in findings from previous studies, which suggested that attentional resources are allocated to expected distractor locations before they can be ignored, constituting a major factor in the failure to filter irrelevant information (i.e., the attentional white bear phenomenon; Benoni, ; Humphreys, Stalmann, & Oliviers, ; Lahav, Makovski, & Tsal, ; Lahav & Tsal, ; Tsal & Makovski, ). Another option is that the filtering setting may simply deteriorate with time.…”
Section: Discussionmentioning
confidence: 99%